Tumor hybrid cells in non-small cell lung cancer: population structure and contribution to prognosis - Anna A. Khozyainova; Maxim E. Menyailo; Maria S. Tretyakova; Ustinia A. Bokova; Anastasia A. Korobeynikova; Tatiana S. Gerashchenko; Evgeny O. Rodionov; Sergey V. Miller; Evgeny V. Denisov (RUDN Journal of Medicine)
Relevance. Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related mortality worldwide due to the high recurrence and metastasis rates. It is generally accepted that metastases and recurrences are formed by tumor cells with a highly invasive, stem and chemoresistant phenotype. Tumor hybrid cells (THCs) formed by the fusion of tumor cells with a wide range of normal cells: macrophages, fibroblasts, mesenchymal stem cells, etc. are considered to be potential metastasis and recurrence-initiating cells. However, the phenotypic diversity of THCs, and their association with disease progression remain poorly understood. The aim of the study was to characterize the population composition of THCs in NSCLC and its association with clinicopathological characteristics, metastasis and recurrence. Materials and Methods. A total of 50 patients with NSCLC were included. Fresh frozen samples of tumor tissue obtained during resection and morphologically verified were used to analyze types and number of THCs. THCs were analyzed by flow cytometry in primary tumors using markers for tumor cells, cancer stem cells, leukocytes, macrophages and fibroblasts. Results and Discussion. THCs were detected in all NSCLC patients. Most THCs demonstrated leukocyte, macrophage and stem characteristics. The number and frequency of THCs depended on neoadjuvant chemotherapy. THCs with leukocyte and stem cell markers (pan-CK+CD45+CD44+CD73+) were associated with locoregional recurrence, whereas THCs with macrophage and stem cell markers (EpCAM+CD45+CD44+CD73+CD163+) — with distant metastases. Conclusion. This study is the first to comprehensively describe the population composition of THCs in NSCLC, their association with clinicopathological characteristics, neoadjuvant chemotherapy and disease prognosis. Detection of prognostically relevant THCs could be an effective approach for predicting the risk of metastasis and recurrence of NSCLC and the basis for the development of therapy focused on the prevention of cancer progression.